Hubungan Antara Lingkungan Kerja Non Fisik dengan Kepuasan Kerja Karyawan - Pratiwi, Linda; , Drs. Mohammad Amir,M.Si (2017)
The issue of job satisfaction is a question that can not be ignored in the industrial field nowaday. Employees who are not satisfied can have a bad effect on the company. Decreased productivity of the company because employees often complain, not serious in work, and make some mistakes in their work, One of the variables that contribute to employee satisfaction is the work environment it self. From that the hypothesis proposed: there is a positive relationship between the non-physical work environment with job satisfaction. The subject of this research is 75 employees of Angkasa Pura I Adi sumarmo International Airport. The sampling technique used in this research is Quota non random sampling. Data collection using the Scale of non-physical work environment and job satisfaction, data analysis methods using product moment correlation techniques. The result of data analysis: correlation value (r) 0,543 with significant 0,000 (p <0,01) mean there is a significant positive relation between non-physical work environment with job satisfaction. The contribution of non-physical work environment to job satisfaction is 29,4% and there are 70,6% other factors that influence job satisfaction outside non-physical working environment. Based on result of categorization calculation, non-physical working environment of research subject is classified either by mean or mean Empirical (RE) of 149.24 and hypothetical average (RH) of 120. Job satisfaction of research subjects is high shown by empirical average (RE) of 113.96 and hypothetic average of = 82.5.